Multi-Locus Sequence Analysis Reveals Diversity of the Rice Kernel Smut Populations in the United States - Sabin Khanal; Sanjay Antony-Babu; Shankar P. Gaire; Xin-Gen Zhou (Frontiers in Microbiology, 2022)
Rice (Oryza sativa) is the second leading cereal crop in the world and is one of the most important field crops in the US, valued at approximately $2.5 billion. Kernel smut (Tilletia horrida Tak.), once considered as a minor disease, is now an emerging economically important disease in the US. In this study, we used multi-locus sequence analysis to investigate the genetic diversity of 63 isolates of T. horrida collected from various rice-growing areas across in the US. Three different phylogeny analyses (maximum likelihood, neighbor-joining, and minimum evolution) were conducted based on the gene sequence sets, consisting of all four genes concatenated together, two rRNA regions concatenated together, and only ITS region sequences. The results of multi-gene analyses revealed the presence of four clades in the US populations, with 59% of the isolates clustering together. The populations collected from Mississippi and Louisiana were found to be the most diverse, whereas the populations from Arkansas and California were the least diverse. Similarly, ITS region-based analysis revealed that there were three clades in the T. horrida populations, with a majority (76%) of the isolates clustering together along with the 22 Tilletia spp. from eight different countries (Australia, China, India, Korea, Pakistan, Taiwan, The US, and Vietnam) that were grouped together. Two of the three clades in the ITS region-based phylogeny consisted of the isolates reported from multiple countries, suggesting potential multiple entries of T. horrida into the US. This is the first multi-locus analysis of T. horrida populations. The results will help develop effective management strategies, especially breeding for resistant cultivars, for the control of kernel smut in rice.